Proceedings of the Second Workshop on Language Technology for Equality, Diversity and Inclusion 2022
DOI: 10.18653/v1/2022.ltedi-1.42
|View full text |Cite
|
Sign up to set email alerts
|

NAYEL @LT-EDI-ACL2022: Homophobia/Transphobia Detection for Equality, Diversity, and Inclusion using SVM

Abstract: Analysing the contents of social media platforms such as YouTube, Facebook and Twitter gained interest due to the vast number of users. One of the important tasks is homophobia/transphobia detection. This paper illustrates the system submitted by our team for the homophobia/transphobia detection in social media comments shared task. A machine learning-based model has been designed and various classification algorithms have been implemented for automatic detection of homophobia in YouTube comments. TF-IDF has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A study implemented neural network using sentence embedding and ensemble model in Tamil, English and Tamil-English [4]. Some of the studies implemented different classification algorithms using TF-IDF to classify the YouTube comments as homophobic and transphobic in English, Tamil and Tamil-English [5]. Similarly, the combination of word embeddings and Support Vector Machine (SVM) are implemented along with BERT-based models in English, Tamil and English-Tamil [7].…”
Section: Related Workmentioning
confidence: 99%
“…A study implemented neural network using sentence embedding and ensemble model in Tamil, English and Tamil-English [4]. Some of the studies implemented different classification algorithms using TF-IDF to classify the YouTube comments as homophobic and transphobic in English, Tamil and Tamil-English [5]. Similarly, the combination of word embeddings and Support Vector Machine (SVM) are implemented along with BERT-based models in English, Tamil and English-Tamil [7].…”
Section: Related Workmentioning
confidence: 99%
“…Different machine-learning classification models were applied to train the data. The set of classification algorithms that have been used are listed below 4 .…”
Section: Modelmentioning
confidence: 99%
“…The F1-scores for the Tamil datasets were 0.40, 0.85, and 0.89. Asraf et al [9] made models using algorithms for machine learning like Svm Algorithm, Random Forest, Passive Aggressive.. Just on data -sets provided as a part of the shared task LT-EDI-ACL2022 [10], they found that SVM was more accurate.…”
Section: Literature Surveymentioning
confidence: 99%